Digital allergology: Towards a clinical decision support system for allergen immunotherapy. (3rd February 2020) - Matricardi, Paolo Maria; Potapova, Ekaterina; Forchert, Leandra; Dramburg, Stephanie; Tripodi, Salvatore
Abstract: Mobile health is the "medical and public health practice supported by mobile devices, such as mobile phones, patient monitoring devices, personal digital assistants, and other wireless devices." For example, mobile apps (such as MASK‐Air, Allergy.Monitor, Pollen, and others) have proven useful in the management of patients with allergic rhinitis. These apps can be used in the context of broader clinical decision support systems (CDSS) for enhancing allergy‐related decisions and actions with pertinent, organized clinical knowledge and patient information to improve allergy care. A CDSS targeted to control rhinitis with drugs and other interventions guiding the patient in his/her self‐ and doctor‐driven management is currently being produced and investigated by the MACVIA network. Another one, called @IT‐2020, is targeted to support etiologic diagnostics and allergen immunotherapy (AIT) prescriptions for patients with seasonal allergic rhinitis. Intensive investigation is necessary to better define the advantages and limitations of mobile‐health technology in allergology and establish guidelines for their proper use in daily practice in the context of a rapidly evolving European regulatory environment.